Sensibilidade de cultivares de soja a sulfentrazone + diuron aplicado em solo com e sem palha - Guadgnin, Raquel Alice (2022)
Soybean is one of the main crops, with many recorded abiotic and biotic factors that can create occasions. Among the factors that make resistance or tolerance to herbicides stand out, plants with problems of resistance or tolerance to herbicides stand out. One of the current control alternatives is the use of pre-emergent herbicides or even a mixture of these, such as sulfentrazone + diuron. However, despite the positive aspects of these products, it is essential that it does not affect the germination, growth and development of soybeans. From this observation of sensitivity of the culture to these products, there is a need to test the veracity of this hypothesis in cultivars frequently sown in Rio Grande do Sul. The objective of this work was to study the sensitivity of soybean cultivars to the formulated mixture of sulfentrazone + diuron. The experiments were carried out in the laboratory and in the experimental area of the Univerisade de Passo Fundo – UPF. In the experiment carried out in the laboratory, BMX Ativa, DM595 and TMG7062 were tested as soybean cultivars, exposed as Oper (0; 0.1; 1.0; 5.0; 10; 25 and 50 mg.L-1) of the mixture of sulfetrazone diuron in a completely randomized design, arranged in a factorial scheme x 7, with four replications. Note that soybean cultivars are sensitive to a mixture of sulfentrazone + diuron applied pre-emergence of the crop. In the field study of the different study, cultivars were tested in the same way, however, with doses of the mixture of sulzone study + diuron previous study (0; 0.7; 1; 1.2; 1.4; 1, 6 and 1.8 L.ha-1), arranged in sub-divided plots, in the plot allocated the managements (with and without straw), in the sub-plot the cultivars and in the sub-plots the doses of the herbicide. As estimates were visual phytotoxicity, crop emergence, plant height, leaf area index, biomass, grain yield components and grain yield. As a cultivar that was less sensitive to the herbicide mixture, regardless of the dose and soil management, or without straw, for grain yield, it was DM5958. Therefore, it is concluded that the selectivity is dependent on several factors, dynamics of the herbicide in the environment, physical-chemical characteristics of the herbicide and biological capacity of plants to metabolize.